Probation and Parole Officers' Outlook on the Proposed GPS Toolkit: Focus Groups on the Potential of Proposed Tools for TRACKS in Oklahoma, 2011 - Yuan, May ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed.The purpose of the Probation/Parole Officer's (PPO) portion of the study was designed to capture work experiences, caseload, and several important issues related to information systems assimilation (i.e., work environment, caseload, technical support, system reliability and consistency, perceived usefulness of information and system, perceived ease of use, attitude toward the current GPS system and the program, intention to use, actual use, access to system, flexibility of the system to adapt to user needs, integration of information into other agency processes, quality of output, comprehensiveness of information provided, format of the system display and output provided, timeliness of obtaining the information, speed of system operation, overall satisfaction with monitoring system, training provided, value added to the officers efforts by the monitoring system, and ease of learning to use the system).The single data file (PPO_survey_data_9182014.sav) contains 102 variables and 55 cases.